The butterfly suture technique for meniscal repair - Gunes, Taner; Bostan, Bora; Erdem, Mehmet; Asci, Murat; Sen, Cengiz; Kelestemur, Mehmet Halidun (Springer, 2011)
One of the important factors effecting meniscal healing is the strength of primary fixation obtained by repairing technique. From this perspective, it is important to choose the technique ensuring a higher primary fixation strength for meniscal repairs. We described a new technique for meniscal repair called butterfly technique using Viper device and hypothesized that high primary fixation strength can be obtained with this technique. The study was performed on calve knees. Full-thickness longitudinal tears 2 cm in length and 3 mm medial from the periphery were created in corpora of medial menisci of 14 calves. After creating tears, menisci were divided into two equal groups. In Group 1, two vertical loop sutures 1 cm apart were placed using a Viper device. Whereas in Group 2, tears were repaired using butterfly sutures. The mean load to failure was 156.3 +/- A 13.1 and 186 +/- A 15.8 N in Group 1 and 2, respectively (p = 0.002). The fixation strength in Group 2 was significantly higher than in Group 1. We suggest that, using Viper device and all-inside butterfly suturing techniques, meniscal ruptures with appropriate locations can be repaired with higher primary fixation strength.
Keywords: Meniscus; Repair; Butterfly technique; Viper device